Dispersion Optimization of Silicon Nitride Waveguides for Efficient Four-Wave Mixing - Yaping Hong; Yixiao Hong; Jianxun Hong; Guo-Wei Lu (Photonics, 2021)
Silicon nitride waveguides have emerged as an excellent platform for photonic applications, including nonlinear optical signal processing, owing to their relatively high Kerr nonlinearity, negligible two photon absorption, and wide transparent bandwidth. In this paper, we propose an effective approach using 3D finite element method to optimize the dispersion characteristics of silicon nitride waveguides for four-wave mixing (FWM) applications. Numerical studies show that a flat and low dispersion profile can be achieved in a silicon nitride waveguide with the optimized dimensions. Near-zero dispersion of 1.16 ps/km/nm and 0.97 ps/km/nm at a wavelength of 1550 nm are obtained for plasma-enhanced chemical vapor deposition (PECVD) and low-pressure chemical vapor deposition (LPCVD) silicon nitride waveguides, respectively. The fabricated micro-ring resonator with the optimized dimensions exhibits near-zero dispersion of −0.04 to −0.1 ps/m/nm over a wavelength range of 130 nm which agrees with the numerical simulation results. FWM results show that near-zero phase mismatch and high conversion efficiencies larger than −12 dB using a low pump power of 0.5 W in a 13-cm long silicon nitride waveguide are achieved.